Manajemen Pembiayan dalam Meningkatkan Mutu Pembelajaran pada MTsN 7 Madiun - Kholis Masroatin Nafiah (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2024)
Indonesia's education sector, including basic education, faces a range of challenges, ranging from low allocation of government financial support to a lack of training to improve teachers' professional abilities amid Indonesia's small education budget. The purpose of this study is to know and analyze financing management in improving the quality of learning in MTsN 7 Madiun. The method used in research is a qualitative approach using descriptive methods. Data collection techniques include interviews, observation, and documentation. While analyzing the data by data reduction, display, and conclusion. The conclusion is: (1). The head of the madrasah is responsible for planning the financial resources of education in accordance with the position given to him by the government (2). The education financing approach prioritizes the most important madrasah needs to improve the quality and quality of education (3). Education funding is monitored by external and internal accredited bodies (4). The obstacles faced are, first, the scheme is different from the dues received from the government, and second, the payment of funds to the madrasah committee is not routinely carried out by a small number of parents' associations.